PENERAPAN MODEL GUIDED DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 22 PADANG - ANNISA SARAH (Departemen Matematika, 2020)
Understanding of mathematical concepts is one of the objectives learning needs to be achieved. But in fact the understanding of the mathematical concept of learners class IX SMP Negeri 22 Padang is still not optimal. To overcome this problems, it was needed a method or approach that make students be able to construct their own concepts. One model that can be used was the guided discovery learning model. This study aimed to see the effect of using guided discovery learning models on the understanding of mathematical concepts of grade IX students of SMP Negeri 22 Padang. And to describe the attitudes and skills of students in class IX SMP Negeri 22 Padang using the Guided Discovery Learning model. The types of research used are pseudo experiments (Quasy experiment) with the research design of The Non-equivalentwPosttest-Only Control Group Design, with a population of class IX and samples of two classes of IX. 1 and IX. 4 SMP Negeri 22 Padang. The experimental class was given learning by using the guided discovery learning model that has special syntax, namely motivation and problem statements, data collection, data processing, verification and closure. The control o class used a direct learning. The instrument used was a learning achievement test that contained criteria for concepts understanding and judged on the concept of scoring. The statistical test used is test-t. The of data processing showed the price of count > t table, this means that H0 was rejected and H1 was accepted. It can be concluded that learning with discovery learning models affects they understanding of mathematical concepts at SMP N 22 Padang.As well as the progression of the students ' attitudes and skills assessments using guided discovery learning are on good criteria at each meeting. Keywords: guided discovery learning, understanding of mathematical concepts, direct learning